Toward Exact Critical Exponents from the low-order loop expansion of the Effective Potential in Quantum Field Theory - Abouzeid M. Shalaby (16810695) (2024)
The asymptotic strong-coupling behavior as well as the exact critical exponents from scalar field theory even for the simplest case of 1 + 1 dimensions have not been obtained yet. Hagen Kleinert has linked both critical exponents and strong coupling parameters to each other. He used a variational technique ( back to kleinert and Feynman) to extract accurate values for the strong coupling parameters from which he was able to extract precise critical exponents. In this work, we suggest a simple method of using the effective potential ( low order) to obtain exact values for the strong-coupling parameters for the ϕ4 scalar field theory in 0 + 1 and 1 + 1 space–time dimensions. For the 0 + 1 case, our results coincide with the well-known exact values already known from literature while for the 1 + 1 case we test the results by obtaining the corresponding exact critical exponent. As the effective potential is a well-established tool in quantum field theory, we expect that the results can be easily extended to the most important three dimensional case and then the dream of getting exact critical exponents is made possible. Other Information Published in: Annals of Physics License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.aop.2024.169786